(untitled) (Advances in Applied Biological Research, 2025)
Vitamin C (ascorbic acid) is a water-soluble vitamin with vital roles in human health. It functions as a potent antioxidant, supports the immune system, aids in collagen synthesis, and enhances iron absorption. The deficiency of vitamin C leads to scurvy, while its adequate intake is associated with numerous health benefits, including reduced risk of chronic diseases such as cardiovascular disease, cancer, and neurodegenerative disorders. Supplementation with vitamin C appears to be able to both prevent and treat respiratory and systemic infections. This review provides an analysis of the role of vitamin C in health and disease, its dietary sources, recommended intake, and its therapeutic applications based on recent literature.